PENGELOLAAN KOPERASI PEGAWAI NEGERI - Safitri, Siska Nur; Nugroho, Piter Joko; Ernawatie (Equity In Education Journal, 2024)
This research aims to describe the Management of the State Employee Cooperative (KPN) "Sejahtera" at MTsN 2 Kota Palangka Raya. This research uses a qualitative approach with a case study design. Through purposive sampling technique, the data sources in this study were determined, including: Chairman, Secretary, Treasurer and Members of the cooperative. Data were collected through observation, interview, and study of document techniques. Data analysis used an interactive data model. Data validation using triangulation and member check techniques. The results showed that good management of KPN "Sejahtera" plays an important role in achieving cooperative goals, which not only improves the welfare of its members but also strengthens solidarity and social cohesion among its members. The application of professional and member-oriented management is the key to success in achieving the objectives of KPN "Sejahtera" at MTsN 2 Kota Palangka Raya.